Perlindungan Hukum Terhadap Anak TKI Dalam Tindak Pidana Pencurian Di Kabupaten Blitar - Rukmono, Indra; Putera, Rizky Perdana Bayu; Irawati, Irawati (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
This study analyzes the legal protection of children of Indonesian Migrant Workers (TKI) who become victims of theft in Blitar Regency. These children are particularly vulnerable and require adequate protection to ensure their rights and safety. Using an empirical legal method with a descriptive approach, data were collected through interviews, analysis of relevant laws, and case document reviews. The findings indicate that despite existing legal frameworks, implementation remains weak due to limited public awareness and inadequate law enforcement. Challenges also arise from the lack of cooperation among institutions and insufficient resources. The study recommends strengthening legal education on children's rights, enhancing institutional collaboration, and improving the capacity of legal authorities in handling cases involving TKI children. These efforts are essential to ensure more effective legal protection and to prevent further victimization of children in similar situations.